2009
DOI: 10.1074/jbc.m109.032714
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Human Epidermal Growth Factor Receptor Signaling with the Neuregulin's Heparin-binding Domain

Abstract: Neuregulin (NRG)2 has been shown to have a wide array of functions with important roles in nervous system and heart development as well as in diseases ranging from breast cancer to schizophrenia (1-4). It mediates its diverse effects through binding homo-and heterodimeric cell-surface epidermal growth factor receptors, including HER2(erbB2), HER3(erbB3), and HER4-(erbB4), that leads to rapid receptor-tyrosine phosphorylation and activation of downstream signaling pathways, including the mitogen-activated prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…In fact, fusion proteins containing the Ig-like heparin binding domain from neuregulin retains heparin binding capacity, although at different affinities depending on the requirement of a spacer domain and where it fits into the context of the rest of the protein (26). Despite this, TPV-15L retains the functional capacity to bind heparin, which may be an indication of potential targeting and function of the molecule.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, fusion proteins containing the Ig-like heparin binding domain from neuregulin retains heparin binding capacity, although at different affinities depending on the requirement of a spacer domain and where it fits into the context of the rest of the protein (26). Despite this, TPV-15L retains the functional capacity to bind heparin, which may be an indication of potential targeting and function of the molecule.…”
Section: Discussionmentioning
confidence: 99%
“…SPGF, on the other hand, has yet to be fully characterized, but some data suggest that ErbB1 is necessary for signal transduction (25). Here, we describe a fourth member of the EGF-like growth factor family from tanapoxvirus (TPV), encoded by the TPV-15L gene, that is capable of activating the neuregulin receptor heterodimer ErbB2/3 as shown in an established neuregulin bioassay (26). Our initial characterization of this protein has identified heparin binding ability, similar to the case for certain isoforms of mammalian neuregulin.…”
mentioning
confidence: 98%
“…However, a follow-up study indicated that effects of systemically delivered type II NRG1 were less likely due to direct effects on remyelination, but to modulation of the immune response that favors remyelination (Penderis et al, 2003). Given that microglial activation is a common pathological change in both ALS and MS, blocking NRG1 signaling could thus be a therapeutic target to slow disease progression in neurodegenerative diseases including MS. We have developed a targeted neuregulin antagonist (Ma et al, 2009) that given intrathecally reduces microglial activation in rat chronic spinal cord pain model (Calvo et al, 2010). Use of this new reagent could help define at which points during the disease process NRG1 activity is beneficial or harmful.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, NRG1 signaling through activation of erbB2 receptors has been shown to be critical for microglial activation in the dorsal spinal cord of rats that develop chronic pain following peripheral nerve injury (23). Using a novel NRG1 antagonist (45) injected intrathecally, the number of activated microglia was reduced together with mechanical and cold pain-related hypersensitivity (23). These findings suggest that NRG1 is an important, local signal for microglial activation in the spinal cord after neural injury and that blocking NRG1 signaling could be a novel approach to block the untoward effects that ensue.…”
Section: Discussionmentioning
confidence: 99%